The Effect of Environmental, Social, and Governance on Financial Performance of Manufacturing Companies Listed on the Indonesia Stock Exchange (IDX) - Syakilah Suci Fernanda; Dwi Wahyuningsih (Dinasti Publisher, 2025)
This study investigates the simultaneous impact of Environmental, Social, and Governance (ESG) variables on the financial performance of manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2023. A 2020 survey by Globescan and the Global Reporting Initiative (GRI) revealed a significant rise in public trust regarding sustainability report disclosures, with Indonesia ranking first among 27 countries at 81%. Despite this, Indonesia's ESG implementation shows weaknesses in social and environmental responsibility, as reflected in the 2021 Environmental Performance Index (EPI), where Indonesia ranked 22nd out of 25 Asia-Pacific countries in environmental sustainability. This quantitative study utilized documentation techniques and secondary data from the IDX, focusing on 79 companies, with 11 ma.nufacturing firms as the sample. The findings indicate that ESG factors positively affect financial performance, with a significant (Sig) value of 0.000. However, the environmental aspect alone does not significantly impact financial performance (Sig 0.151). In contrast, both social and governance factors show a strong positive effect on financial performance, each with a Sig value of 0.000. These results highlight the importance of social and governance practices in enhancing corporate financial outcomes.